Vitamin D3: The magical solution in the prevention of Covid-19. - Iqbal, Mehir un Nisa; Ahmed, Ayaz; Fatima, Syeda Sadia; Khan, Taseer Ahmed (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
OBJECTIVE: The COVID-19 pandemic has grasped the world in a tight fix. For good public health, strict measurements should be adopted that can help minimize the infection and death risk during the pandemic. Therefore, the present review discusses the postulated mechanism of the protective role of vitamin D3 in decreasing the probability of having COVID-19 infections. METHODOLOGY: The review data was gathered from July 2022 to July 2024 by sourcing relevant scientific literature from various databases using specific keyword combinations related to Vitamin D3 and COVID-19. A total of 515 research papers were reviewed; however, only 42 original articles published from 2020 to 2024 specifically examined the relationship between Vitamin D and COVID-19. RESULTS: The observational studies indicated a significant correlation between vitamin D levels and COVID-19. Conversely, randomized controlled trials suggested that high doses of Vitamin D3 could reduce mortality in COVID-19 patients. Vitamin D3 induces antimicrobial peptides such as cathelicidins (specifically LL-37) and defensins, which may have antiviral activity and can reduce the concentration of pro-inflammatory cytokines while increasing the concentration of anti-inflammatory cytokines. Vitamin D3 boosts innate and adaptive immunity suppresses the renin-angiotensin pathway and stimulates ACE2 expressions. CONCLUSION: Based on the scientific literature, vitamin D3 is beneficial and required to augment the immune-modulatory effects of infected COVID-19 patients. Population-based studies debated the relationship between vitamin D3 levels and COVID-19 cases. However, clinical trials and large epidemiologic and observational studies should still be needed to assess these acclamations.